2003
DOI: 10.1038/nature01837
|View full text |Cite
|
Sign up to set email alerts
|

Dimers of the N-terminal domain of phytochrome B are functional in the nucleus

Abstract: A plant modulates its developmental processes in response to light by several informational photoreceptors such as phytochrome. Phytochrome is a dimeric chromoprotein which regulates various aspects of plant development from seed germination to flowering. Upon absorption of red light, phytochrome translocates from the cytoplasm to the nucleus, and regulates gene expression through interaction with transcription factors such as PIF3 (refs 5-7). The phytochrome polypeptide has two domains: the amino-terminal pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
343
3
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 286 publications
(368 citation statements)
references
References 30 publications
21
343
3
1
Order By: Relevance
“…To evaluate the contribution of cytoplasmic P fr signaling into the circadian system, we introduced the G767R mutation into the YHB allele (YHB-G767R). Phys containing the G767R mutation are retained in the cytoplasm (Wagner and Quail, 1995;Ni et al, 1999;Matsushita et al, 2003). This has been attributed to the inability of the G767R mutant to interact with PIF3 and then be imported into the nucleus (Pfeiffer et al, 2012).…”
Section: Cytosolic Yhb Has Little Effect On Clock Gene Expression or mentioning
confidence: 99%
“…To evaluate the contribution of cytoplasmic P fr signaling into the circadian system, we introduced the G767R mutation into the YHB allele (YHB-G767R). Phys containing the G767R mutation are retained in the cytoplasm (Wagner and Quail, 1995;Ni et al, 1999;Matsushita et al, 2003). This has been attributed to the inability of the G767R mutant to interact with PIF3 and then be imported into the nucleus (Pfeiffer et al, 2012).…”
Section: Cytosolic Yhb Has Little Effect On Clock Gene Expression or mentioning
confidence: 99%
“…Autophosphorylation is a common property of all photosensory pigments including phytochromes and phototropins (Christie 2007). However, it also appears that the autokinase activity is dispensable for both phytochrome (Matsushita et al 2003) and phototropin (Kagawa et al 2004) functions. It was found that both AtCRY1 and AtCRY2 are phosphorylated in vivo upon blue light exposure (Shalitin et al 2002;.…”
Section: Protein-protein Interactionsmentioning
confidence: 99%
“…Studies of photobody localization using Arabidopsis phyB have shown that the C-terminal domain of phyB is involved in dimerization and is sufficient for both nuclear and photobody localization (Matsushita et al, 2003;Chen et al, 2005). When the C-terminal domain of phyB is replaced with a dimerization domain, a Simian Vacuolating Virus40 nuclear localization signal, and GFP, the chimeric protein, NGB (for the N-terminal half of phyB fused to GFP), does not localize to photobodies (Matsushita et al, 2003).…”
mentioning
confidence: 99%
“…Most loss-of-function phyB alleles are defective in phyB localization to large photobodies and are taller than the wild type (Kircher et al, 2002;Chen et al, 2003;Matsushita et al, 2003;Nito et al, 2013), whereas in gain-of-function phyB mutants, phyB localizes to large photobodies under dim light and hypocotyl elongation is more restricted than in the wild type (Ádám et al, 2011;Medzihradszky et al, 2013;Zhang et al, 2013). In the most extreme case, phyB Y276H (YHB), a constitutively active phyB mutant, localizes to large photobodies regardless of light conditions and can inhibit hypocotyl growth even in the dark (Su and Lagarias, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation